Development and Validation of UV Spectroscopic Method for the Quantification of Lamotrigine in Bulk and Marketed Formulations - Chagi, Madhusri; Srinivasulu, Neeladri; Anand Kumar, Yegnoor; Polkal, Pooja; Shetty, Keerthana (Asian Journal of Pharmaceutical Research and Development, 2024)
Two Simple and precise UV spectroscopic methods were developed for the estimation of lamotrigine in bulk and marketed tablets. The methods developed by using two solvent systems viz., Methanol: Distilled water (1:1) and Acetonitrile: 0.1N HCl (1:1) were validated as per ICH guidelines. The two proposed solvent systems validated for linearity, accuracy, precision, robustness, ruggedness and solution stability. The percent recovery in the marketed tablet formulationswere found to be good agreement with the label claim. The methods validated statistically and the results suggest these methods can employed for the routine analysis of lamotrigine in bulk and marketed tablet formulations.